Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17